A Cadaveric Study on the Course of the Cervical Segment of the Internal Carotid Artery and Its Variations - Arumugam, Sangeetha (Cureus, 2020)
Introduction The internal carotid artery is the chief source of blood supply to the brain. Variations of the internal carotid artery, such as curved, kinking, and coiling, might result in significant neurovascular problems due to alterations in the dynamics of blood flow. The elongated and tortuous course of the internal carotid artery in the cervical region has a high chance of being damaged during head and neck surgeries. Method The study aims to observe the course and variations of the internal carotid artery in 50 cadaveric hemi-neck specimens of both sexes. The internal carotid artery was traced from its origin until its termination in the base of the skull. Variations in the course, position, and the level of the carotid bifurcation were observed and analysed. Result Out of the 50 specimens, a higher carotid bifurcation was observed in 40% of the specimens and 28% showed variations in the course, such as curved (18%), kinking (8%), and coiling (2%). The position of the internal carotid artery was reversed in 16% of the specimens. Conclusion Curved, kinking, and coiling types of carotid artery variations observed in the present study had right-sided and female predominance. Knowledge about such variations is essential for the diagnosis and management of neurological disorders and in head and neck surgeries.